2015
DOI: 10.1021/acsami.5b04290
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Influences Cellular Uptake of Gold Nanoparticles by Phagocytic and Nonphagocytic Cells in a Size-Dependent Manner

Abstract: The interaction at nanobio is a critical issue in designing safe nanomaterials for biomedical applications. Recent studies have reported that it is nanoparticle-protein corona rather than bare nanoparticle that determines the nanoparticle-cell interactions, including endocytic pathway and biological responses. Here, we demonstrate the effects of protein corona on cellular uptake of different sized gold nanoparticles in different cell lines. The experimental results show that protein corona significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
219
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(226 citation statements)
references
References 34 publications
5
219
2
Order By: Relevance
“…HP and HSA coronas decreased hepatocyte uptake of all bare 40 and 80 nm BPEI-and LA-AuNP and 80 nm PEG-AuNP at 12 h and 24 h, but showed an increase in cell uptake for 40 nm PEG-AuNP ( Figure 4(A-F)). An inhibitory effect of serum coronas on the uptake of AuNP with hexadecyltrimethyl ammonium bromide-Au nanorods and poly (4-styrene sulfonic acid)-Au-nanorods in HeLa cells (Hauck et al, 2008); and citrate-AuNP in HepG2 and RAW 264.7 (Cheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HP and HSA coronas decreased hepatocyte uptake of all bare 40 and 80 nm BPEI-and LA-AuNP and 80 nm PEG-AuNP at 12 h and 24 h, but showed an increase in cell uptake for 40 nm PEG-AuNP ( Figure 4(A-F)). An inhibitory effect of serum coronas on the uptake of AuNP with hexadecyltrimethyl ammonium bromide-Au nanorods and poly (4-styrene sulfonic acid)-Au-nanorods in HeLa cells (Hauck et al, 2008); and citrate-AuNP in HepG2 and RAW 264.7 (Cheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Human serum albumin (HSA) and IgG coronas enhanced cellular uptake of citrate coated AuNP in human umbilical vein endothelial cells (HUVEC) compared to fibrinogen . Serum coated AuNP reduced NP cellular uptake in HepG2 and murine macrophages (Cheng et al, 2015). AuNP with tannic acid inhibited CYP2C9, CYP2C19, CYP2D6 and CYP3A4 activities in human liver microsomes (Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies investigated the role of either size, surface chemistry or the presence of a protein corona on cell uptake of AuNP (Cheng et al, 2015;Choi et al, 2017;Freese et al, 2012;Li & Monteiro-Riviere, 2016;Mirsadeghi et al, 2015;Monteiro-Riviere et al, 2013;Sasidharan et al, , 2016. However, there is lack of information on the definite links between the NP physicochemical properties, signature biocorona adsorbomes, cell uptake patterns, toxicity and gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…22 Since the PC affects the properties of the NP surface, it has significant impact on the interaction between membrane and NPs. [23][24][25][26][27] Many studies are described in the literature where NP cellular uptake is related to the presence of a PC on the NPs in biological fluids, [28][29][30] in particular it has been shown that a key factor in NPs cellular uptake is their adhesion to the cell membrane that significantly affects their final uptake rates. 31 NP-cell membrane interaction is a complex dynamic process in which the environmental proteins are known to play an important multifaceted role: not only they adsorb onto the NP surface forming the PC, but also they compete with the NP in the interaction with the cell membrane.…”
Section: Introductionmentioning
confidence: 99%